“At the Heart of Culture?” Constructing the ‘Creative City’ Through Logomo - Huopalainen, Astrid; Tailas, Jutta (Scandinavian Journal of Public Administration, 2014)
This paper explores the complexity of meanings of the ‘creative city’ through multiple understandings of space. We explore how meanings attached to a novel, material space called Logomo, established in the city of Turku in Finland, European Capital of Culture in 2011, play out in the construction and performing of the city as ‘creative’. We understand space as socially, materially and imaginarily constructed and here, connect the notion of space to the dominantly deterministic and problematic creative city debate. More specifically, we examine those multiple ways in which meanings of a ‘creative city’ in transition are socially constructed through different representations of space. In addition, we show space in the making: how meanings of Logomo are constructed through those representations, thus creating certain ideas of space Logomo. By questioning ideas central to the normative creative city debate, our study shows how space matters in the ongoing making of a ‘creative city’. As such, this study attempts to contribute to the critically oriented research on spatiality in organization. We show, however, how representations of space ironically seem to reconstruct mainstream notions of a ‘creative city’.